If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -8x = -24 Solving 24 + -8x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -8x = -24 + -24 Combine like terms: 24 + -24 = 0 0 + -8x = -24 + -24 -8x = -24 + -24 Combine like terms: -24 + -24 = -48 -8x = -48 Divide each side by '-8'. x = 6 Simplifying x = 6
| 3x+6x-2=1 | | -147-x=-10x+60 | | 14-k=-k-2k | | (2x-5)+(6x^2-6x-11)= | | -4+5a=4a-2 | | -147-x=-10x+50 | | x+8=-11+2x-6+4x | | 8x-55=45+3x | | 3u^3-6u^2= | | 2a+21=8a+9 | | -8x-55=45+3x | | 24o=(-36) | | (2x-5)(6x^2-6x-11)= | | -124+12x=4x+44 | | 4x+1=5x^2 | | 100-55x=3 | | 4x+1=x^2 | | -114+10x=-2x+138 | | 4=3t-5 | | -9x-29=-11x+9 | | -8+x-2+3x=x | | 7y-8y=6y+1 | | 9x-40=62+3x | | -78+11x=69+4x | | 3s-14=16 | | 5c=-7 | | 19a^6-57a^7= | | -x-1=2x | | (3b+2)(3b-2)= | | 2m+2=3m | | 2(-7+4x)=82 | | 9x^3+27x^2+45x= |